Self-consistent time dependent vibrational and free electron kinetics for CO2 dissociation and ionization in cold plasmas. (31st March 2017) - Capitelli, M; Colonna, G; D'Ammando, G; Pietanza, L D
Abstract: A self-consistent time dependent model, based on the coupling between the Boltzmann equation for free electrons, the non equilibrium vibrational kinetics for the asymmetric mode of CO2 and simplified global models for the dissociation and ionization plasma chemistry, has been applied to conditions which can be met under pulsed microwave (MW), dielectric barrier discharge (DBD) and nanosecond pulsed discharges (NPD). Under MW discharge type conditions, the selected pulse duration generates large concentration of vibrational excited states, which affects the electron energy distribution function (eedf) through the superelastic vibrational collisions. Moreover, in discharge conditions, plateaux appear in the vibrational distribution function (vdf) through the vibrational–vibrational up pumping mechanism, persisting also in the post discharge. In post discharge conditions, also the eedf is characterized by plateaux due to the superelastic collisions between cold electrons and the CO2 electronic state at 10.5 eV. The plateau in vdf increases the dissociation of pure vibrational mechanism (PVM), which can become competitive with the dissociation mechanism induced by electron molecule collisions. The PVM rates increase with the decrease of gas temperature, generating a non-Arrhenius behaviour. The situation completely changes under DBD and NPD type conditions characterized by shorter pulse duration and higher applied E / N values. Under discharge conditions, both vdf and eedf plateaux disappear, reappering in the afterglow.